2007 International Symposium on Communications and Information Technologies 2007
DOI: 10.1109/iscit.2007.4392128
|View full text |Cite
|
Sign up to set email alerts
|

On statistics of the mobile rayleigh fading channel in non-isotropic scattering environments

Abstract: Scattering encountered in many wireless communications scenarios is non-isotropic. Assumption of uniform distribution of Power Azimuth Spectrum (PAS) in a non-isotropic scattering environment introduces significant errors on the second order channel statistics which are the basis for the estimation of some important receiver parameters. Moreover, there are certain applications in communications that rely solely on the statistics of the channel. In this contribution, we use the wellknown Jacobi-Anger expansion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In addition, it has also been demonstrated that an AS of 60 is sufficient to achieve a system capacity close to the limit that corresponds to isotropic scattering [18]. The AS of a uniform distribution of the power in all angles corresponds to [9]. The AS is in fact confirmed to have an important effect on final MIMO capacity from Fig.…”
Section: Mimo Capacity Resultsmentioning
confidence: 72%
“…In addition, it has also been demonstrated that an AS of 60 is sufficient to achieve a system capacity close to the limit that corresponds to isotropic scattering [18]. The AS of a uniform distribution of the power in all angles corresponds to [9]. The AS is in fact confirmed to have an important effect on final MIMO capacity from Fig.…”
Section: Mimo Capacity Resultsmentioning
confidence: 72%